Training Intervention - a Need for Joint forest Management - Rastogi, Alind (Indian Forester, 1994)
The Concept of Joint Fored Management is sweeping the entire nation with the advent of New Forest Policy. For effective institutionalization of JFM there is a need to equip the forest department officials with necessary technical knowledge, skill and attitudes. A stock of these necessary skills and knowledge has been evolved after a survey where view point of forest official, people and NGO5 were accommodated and compiled. It is thus imperative to incorporate suitable chaneges into the syllabus for the training of foresters so as to equip them to manage the change in an effective manner.